Adiponectin, Leptin, and Fatty Acids in the Maintenance of Metabolic Homeostasis Through Adipose Tissue Crosstalk - Stern, Jennifer H. (Cell Metab, 2016)
Metabolism research has made tremendous progress over the last several decades in establishing the adipocyte as a central rheostat in the regulation of systemic nutrient and energy homeostasis. Operating at multiple levels of control, the adipocyte communicates with organ systems to adjust gene expression, glucoregulatory hormone exocytosis, enzymatic reactions and nutrient flux to equilibrate the metabolic demands of a positive or negative energy balance. The identification of these mechanisms has great potential to identify novel targets for the treatment of diabetes and related metabolic disorders. Herein, we review the central role of the adipocyte in the maintenance of metabolic homeostasis highlighting three critical mediators: adiponectin, leptin, and fatty acids.